2014
DOI: 10.2310/8000.2013.131280
|View full text |Cite
|
Sign up to set email alerts
|

Trends in use in a Canadian pediatric emergency department

Abstract: Introduction: Emergency department (ED) crowding is a significant problem in Canada and has been associated with decreased quality of care in general and pediatric emergency departments (PEDs). Although boarding of admitted patients in the ED is the main contributor to adult ED overcrowding, factors involved in PED crowding may be different. The objective of this study was to report the trend in PED services use and to document the degree of overcrowding experienced in a Canadian PED. Methods: A retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 15 publications
1
29
0
1
Order By: Relevance
“…4 Previous review of our PED utilization pattern over the same study period found no significant changes in acuity distribution using the CTAS. 35 This would suggest that the observed trends in CTAS scores among mental health-related visits likely reflect a change in acuity level distribution rather than alterations in our triaging system or practice. Future studies should address the appropriateness of the CTAS for triaging mental health-related visits to the PED, as it is possible that this tool assesses urgency better than severity, particularly when evaluating chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous review of our PED utilization pattern over the same study period found no significant changes in acuity distribution using the CTAS. 35 This would suggest that the observed trends in CTAS scores among mental health-related visits likely reflect a change in acuity level distribution rather than alterations in our triaging system or practice. Future studies should address the appropriateness of the CTAS for triaging mental health-related visits to the PED, as it is possible that this tool assesses urgency better than severity, particularly when evaluating chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a Canadian retrospective study on PED use in British Columbia reports that during a period where annual PED visits increased by 30%, visits triaged CTAS 1 and CTAS 3 remained constant (<10% increase), whereas CTAS 2 doubled, CTAS 4 increased by 30%, and CTAS 5 nearly quadrupled. 29 We identified that 4.7% of our population had five or more visits to the PED. This group of patients accounted for 16.6% of the total ED visits.…”
Section: Discussionmentioning
confidence: 93%
“…The number of visits at a Canadian pediatric hospital ED between 2002 and 2011 increased by 30%. 2 The increased use of ED services is recognized as a contributor to crowding. Other factors include delays in patient transfer from the ED, limited primary care access, and ED staff training limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…primary cause of overcrowding in general emergency departments, increasing visit volumes and operational inefficiencies appear to drive overcrowding in pediatric emergency departments. 11,12 Studies of overcrowding in pediatric emergency departments have identified important effects on quality of care, including delays in timely use of pain assessment scores for injuries, antibiotic administration for febrile neonates, analgesia for sickle cell crises or long bone fracture, and timely treatment of asthma. [13][14][15] Evidence supporting an association between measures of crowding in the pediatric emergency department and patient outcomes or impact on health care use, however, is lacking.…”
Section: Discussionmentioning
confidence: 99%